Complicated amyotrophic lateral sclerosis - Miguel González-Diaz; Iliana Carrera-Herrera; Amparo Domínguez-Valdivieso (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2024)
Amyotrophic lateral sclerosis is a degenerative neuromuscular disease, it originates when the cells of the nervous system called motoneurons gradually decrease their functioning and die, causing a progressive muscle paralysis of poor prognosis, with low incidence and prevalence of 3 to 5 per 100000 inhabitants and affects people between 40 and 70 years. Motivated by the low incidence of this disease, we decided to present a case assistted at the "María del Carmen Zozaya" hospital in Caibarién. This is a female patient, 53 years old, white, with a history of this condition, with stable treatment, who comes to the guard for fever of 39 °C maintained and productive cough. The examination showed reduced chest expandability, increased vocal vibrations at the right lung base, tingling in the lower right hemithorax region, decreased vesicular murmur with transmitted noises and crackling in the right lung base. Dysarthria, difficulty chewing and swallowing, marked muscle weakness with inability to perform limb movements and difficulties in walking. Chest x-ray: A radiopaque lung lesion in the veil, which occupies the lower lobe of the right lung. Hemogram with differential: hematocrit 0.39 L/L, leukocytes 9.6x109 /L, neutrophils 73, lymphocytes 23, eosinophils 3 and stabs 1; erythosedimentation 84 mm/h, deciding on admission for aspirative pneumonia and amyotrophic lateral sclerosis for treatment and follow-up.